2D Heterostructures Derived from MoS2‐Templated, Cobalt‐Containing Conjugated Microporous Polymer Sandwiches for the Oxygen Reduction Reaction and Electrochemical Energy Storage. Issue 3 (1st February 2017) - Yuan, Kai; Zhuang, Xiaodong; Hu, Ting; Shi, Lei; Sfaelou, Stavroula; Polnick, Ulrike; Forster, Michael; Pichler, Thomas; Riedl, Thomas; Feng, Xinliang; Chen, Yiwang; Scherf, Ullrich
Abstract: Owing to their unique structure and intriguing properties, 2D transition‐metal dichalcogenides (TMDs), such as molybdenum disulfide (MoS2 ), have attracted tremendous attention. Chemical surface functionalization of TMDs can be used to tune their properties and broaden their application perspective. Unfortunately, covalent functionalization of TMDs into sandwich‐type hybrid materials remains challenging, owing to the chemically rather inert basal plane and the poor solution processability of TMDs. Herein, we report an efficient approach for the preparation of MoS2 ‐templated, cobalt‐containing conjugated microporous polymer sandwiches (MoS2 −Co−MP), starting from basal‐plane‐functionalized MoS2 . The resulting MoS2 −Co−CMP hybrids can easily be converted into MoS2 ‐cored, hierarchically porous carbon materials (MoS2 −Co−C) of high specific surface area through direct pyrolysis. The MoS2 −Co−C 2D materials exhibit excellent oxygen reduction reaction activity, approaching the performance of commercial Pt/C catalysts. Moreover, MoS2 −Co−C shows a promising electrochemical energy storage capability, with a high capacitance value up to 288 F g −1 coupled with remarkable cycle stability. Such a promising performance can be attributed to synergistic effects between the MoS2 template and the graphitized, hierarchically porous carbon shells with a homogeneous distribution of nitrogen centres as well as probable involvement of catalytically active Co−N or/and Co−N−C structural motifs. Abstract : Sandwich break : Two‐dimensional, hierarchically porous carbon/MoS2 heterostructures (MoS2 −Co−C) with excellent oxygen reduction reaction activity and promising electrochemical energy storage capability are obtained by pyrolysis and subsequent acid leaching of cobalt‐containing, conjugated microporous polymer/MoS2 (MoS2 −Co−CMP) sandwiches.